1994
DOI: 10.1042/bj3020305
|View full text |Cite
|
Sign up to set email alerts
|

Binding of recombinant annexin V to endothelial cells: effect of annexin V binding on endothelial-cell-mediated thrombin formation

Abstract: Annexin V binds with high affinity to procoagulant phospholipid vesicles and thereby inhibits the procoagulant reactions catalysed by these surfaces in vitro. In vivo, vascular endothelial cells are known to catalyse the formation of thrombin by the expression of binding sites at which procoagulant complexes can assemble. Here, we have studied the binding capacity of recombinant annexin V (rANV) to quiescent, phorbol 12-myristate 13-acetate (PMA)- and tumour necrosis factor alpha (TNF-alpha)-stimulated culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(54 citation statements)
references
References 38 publications
(39 reference statements)
4
50
0
Order By: Relevance
“…AnxA5 binds in a Ca 2ϩ -dependent manner with anionic phospholipids present in membranes of apoptotic cells. AnxA5 binds with high affinity to PS (12). A recent study demonstrated that, in addition to AnxA5, serum protein S specifically binds PS.…”
mentioning
confidence: 99%
“…AnxA5 binds in a Ca 2ϩ -dependent manner with anionic phospholipids present in membranes of apoptotic cells. AnxA5 binds with high affinity to PS (12). A recent study demonstrated that, in addition to AnxA5, serum protein S specifically binds PS.…”
mentioning
confidence: 99%
“…26 However, annexin V binds poorly to curved membranes, 41 requires supraphysiologic Ca ϩϩ concentrations for optimal binding, and inhibits less than 80% of procoagulant function on endothelial cell membranes unless the concentration exceeds 200 nM. 50 Likewise, annexin V is an incomplete inhibitor of the factor Xase complex on platelet membranes. 51 Our results, indicating that inhibition of the prothrombinase complex exceeds 80% at 60 nM annexin V only when the curvature of the membrane is minimal and the PS content is 15%, are in agreement with these prior studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Kd has been reported to have values between 15 and 0.03 nM. [9][10][11] Cooperativity has been reported for the interaction with Ca 2 þ . 12 Freshly isolated, viable monocytes (00h-wo in Figure 1a) as shown by an intact mitochondrial membrane potential (C m ; DiO 6 C), no morphological changes of the nucleus (nSSC), G1/ 0 DNA content (PI-Triton) and no detectable caspase activity (zVAD-fitc) were analysed for their AxV binding in the presence and absence of EDTA.…”
Section: Dear Editormentioning
confidence: 99%